Impact of the ban on uncovered sCDS trade on the interdependencies between the CDS market and other sectors of financial markets: The case of safe and developed versus risky and developing European markets - Agata Kliber (Comparative Economic Research. Central and Eastern Europe, 2016)
The aim of the article is to verify the impact of the ban on uncovered sCDS trade in Europe on the interdependencies between the sCDS market and other sectors of financial markets. We analyse two European markets: the safe and developed Swedish market, and the risky and developing Hungarian one. The study covers the period from October 2008 to October 2013. We analyse changes in the interdependencies between the sCDS market and the bond market, as well as between the sCDS market and the stock exchange. We found out that in the case of the safe Swedish market, the strength of relationships of each sector of financial markets with the sCDS one was much weaker than in the case of Hungary, which may suggest that the Swedish market is less prone to crisis transmission arising from herd behaviour or speculative attacks. In the end we show that in the two economies, the influence of the sCDS market on the other sectors of financial market indeed diminished following introduction of the ban on uncovered sCDS trade.
Keywords: 330; sovereign CDS (sCDS); bonds; exchange rate; stock exchange; volatility; financial crisis